2020
DOI: 10.1002/jimd.12171
|View full text |Cite
|
Sign up to set email alerts
|

Early neurodevelopmental characterization in children with cobalamin C/defect

Abstract: Cobalamin C (cblC) defect is the most common inherited disorder of cobalamin metabolism. Developmental delay, behavioral problems, and maculopathy are common, but they have not been systematically investigated. The aim of this study was to define early neurodevelopment in cblC patients and the possible contribution of different factors, such as mode of diagnosis, age at diagnosis, presence of brain lesions and epilepsy. Children up to the age of 4 years with a visual acuity ≥1/10 were evaluated using the Griff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In a recent study, 18 patients with cblC deficiency underwent neurodevelopmental assessments. The study showed progressive deterioration of the neurodevelopment, identified after 24 months of age 8 . It seems that our patient outcomes may be more favorable compared to previous studies.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In a recent study, 18 patients with cblC deficiency underwent neurodevelopmental assessments. The study showed progressive deterioration of the neurodevelopment, identified after 24 months of age 8 . It seems that our patient outcomes may be more favorable compared to previous studies.…”
Section: Discussionsupporting
confidence: 46%
“…Several recent studies reported neurodevelopmental outcomes in children identified with cblC deficiency on NBS 6‐8,18 . Weisfeld‐Adams described 13 patients with early onset disease (oldest 7 years of age), who had GDD/ID (n = 11), hypotonia (n = 11), nystagmus (n = 8), and thin corpus callosum and white matter abnormalities in brain MRI (n = 9) 6 Hypotonia and nystagmus were more common in that study compared to our study cohort.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The phenotype for disorders of cobalamin metabolism is variable but includes global developmental delay, encephalopathy, neurologic symptoms, and cytopenia [ 3 ]. It has been well documented that newborn screening for methylmalonic acidemia and PA improves outcomes, and more recent studies also show improved outcomes for cblC deficiency [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease results in impaired intracellular synthesis of adenosylcobalamin (Ado-Cbl) and methylcobalamin (Me-Cbl), cofactors for the mitochondrial methylmalonyl-CoA mutase (MUT) and cytosolic methionine synthase (MS) enzymes, respectively (1,2). The clinical consequences are devastating and systemic, including pulmonary problems, hemolytic-uremic syndrome, neurocognitive impairment, and degenerative maculopathy (3)(4)(5)(6). The onset may be early (EO) (a few weeks) or late (LO) (second, third decade of life) (7).…”
Section: Introductionmentioning
confidence: 99%